GENERAL INTRODUCTION TO PAPILLOMA VIRUSES - Pfister, Herbert (CRC Press, 2024)
Warts on the skin and the genitalia have been well-known papillomatous tumors since ancient times. Their viral origin was postulated in 1907 by Ciuffo, 1 who was able to induce common warts in volunteers by injecting them with cell-free filtrates of wart extracts. Successful transmission experiments were also carried out later on with cell-free extracts of condylomata acuminata (genital warts) and laryngeal papillomas. 2 Virus particles were demonstrated by the electron microscope in the upper epithelial layers of these lesions. 3–5 Kreider and colleagues recently infected cervical mucosa biopsies in vitro with virus-positive genital wart extracts and obtained condylomatous proliferations after grafting the tissue beneath the renal capsule of an athymic mouse, 6 which finally proved the oncogenic activity of the virus under controlled experimental conditions.
CRIS-Team Scopus Importer:2025-02-04